Effect of organic amendments on morphological, physiological and root characteristics of red amaranth (Amaranthus gangeticus) grown on Cd contaminated saline soils - Hossain, Mohammad Zaber; Islam, Md Atikul; Islam , Md Azharul; Kibria, Khandoker Qudrata (Bangladesh Journal of Scientific and Industrial Research, 2024)
A pot experiment was conducted to investigate the effects of six different types of organic amendments (OAs) applied to Cd contaminated saline soils with varying rates on red amaranth (Amaranthus gangeticus) growth. Two levels of salinity (4 dSm-1 and 8 dSm-1) were developed in the experimental soil that was previously contaminated with 5 mg kg-1 Cd. In slightly (4 dSm-1) saline soil, 1% vermicompost (VC) produced 18.77 times higher fresh weight as compared to the control while 32.37 times higher found with 2% cowdung (CD). VC produced the maximum fresh weight in moderately saline soil (8dSm-1). Other morphological traits were improved with the addition of OAs. VC increased the plant's relative water content, chlorophyll-a and chlorophyll-b. Root characteristics were improved irrespective of the OA rates and salinity. The efficiency of OAs followed the order VC=CD>compost>WT>SD=RH. Therefore, OA could be a promising way of alleviating the saline soil contaminated with Cd. Bangladesh J. Sci. Ind. Res. 59(3), 149-158, 2024